A decrease in phytic acid content substantially affects the distribution of mineral elements within rice seeds. (September 2015) - Sakai, Hiroaki; Iwai, Toru; Matsubara, Chie; Usui, Yuto; Okamura, Masaki; Yatou, Osamu; Terada, Yasuko; Aoki, Naohiro; Nishida, Sho; Yoshida, Kaoru T.
Highlights: Phytic acid, a seed storage compound of phosphorus, acts as a mineral reservoir. A decrease in phytic acid due to mutation affects the distribution pattern of mineral elements. Phosphorus and potassium were diffused into endosperm from aleurone layer. Zinc and copper became concentrated around the aleurone layer. Abstract: Phytic acid ( myo -inositol hexa kis phosphate; InsP6 ) is the storage compound of phosphorus and many mineral elements in seeds. To determine the role of InsP6 in the accumulation and distribution of mineral elements in seeds, we performed fine mappings of mineral elements through synchrotron-based X-ray microfluorescence analysis using developing seeds from two independent low phytic acid ( lpa ) mutants of rice ( Oryza sativa L.). The reduced InsP6 in lpa seeds did not affect the translocation of mineral elements from vegetative organs into seeds, because the total amounts of phosphorus and the other mineral elements in lpa seeds were identical to those in the wild type (WT). However, the reduced InsP6 caused large changes in mineral localization within lpa seeds. Phosphorus and potassium in the aleurone layer of lpa greatly decreased and diffused into the endosperm. Zinc and copper, which were broadly distributed from the aleurone layer to the inner endosperm in the WT, were localized in the narrower space around the aleurone layer in lpa mutants. We also confirmed that similar distribution changes occurred in transgenic rice with the lpa phenotype. Using these results, we discussed the role of InsP6 in the dynamic accumulation and distribution patterns of mineral elements during seed development.